A Novel Local Control Technique for Converter-Based Renewable Energy Resources in the Stand-Alone DC Micro-Grids - Arash Abedi; Behrooz Rezaie; Alireza Khosravi; Majid Shahabi (Journal of Renewable Energy and Environment, 2020)
This paper presents a novel local control method for the converter-based renewable energy resources in a stand-alone DC micro-grid based on energy analysis. The studied DC micro-grid comprises the renewable energy resources, back-up generation unit, and battery-based energy storage system, which are connected to the common DC-bus through the buck and bidirectional buck-boost converters. The proposed control method satisfies the stability of the micro-grid output variables, along with current control and voltage regulation by controlling the switching functions of the converters, regardless of the energy resource dynamics. The dynamic component of the switching function is extracted as a control signal using the state-feedback through a mathematical method. The control inputs are designed based on Lyapunov stability theorem to guarantee the stability of output variables (DC-bus voltage and generated currents) in a stand-alone DC micro-grid through an energy analysis. The proposed distributed controller can be easily generalized as a platform with all kinds of the stand-alone DC micro-grids comprising any type or number of distributed generations such as renewable energy resources, fossil-fuel-based generations, and energy storage units. Other features of this local control method are simplicity, celerity, comprehensiveness, and independence of the distributed generations. The dynamic performance assessment of the proposed controller is verified through a simulation in MATLAB/SIMULINKÒ environment. The results validate the accuracy and stability of the proposed control strategy in various operating conditions.